Analysis of the inherent adaptability of basic truss and frame modules by means of an extended method of influence matrices. (1st September 2022) - Steffen, Simon; Blandini, Lucio; Sobek, Werner
Highlights: The inherent adaptivity describes how structures can be fundamentally manipulated. This can be analyzed using actuation influence matrices. They present quantitative information on the inducible structural states. Their rank corresponds to the number of manipulatable linearly independent states. This information / method can be used to design adaptive structures intuitively. Abstract: New approaches and technologies are needed to counter the effects of climate change and mitigate the depletion of material resources. A possible solution are adaptive load-bearing structures, i.e., structures that are equipped with sensors, actuators and control units, enabling the structure to optimise its current stress state. This requires new research regarding the overall structural design of material- and emission-efficient adaptive structures. Existing approaches employ sensitivity matrices or optimality criteria in optimization formulations to design adaptive load bearing structures and discuss the quality of the design based on the results. This paper presents the method of actuation influence matrices, which are a type of sensitivity matrix that can be used quantify the inherent adaptability of a structure. The aim is to develop an intuitive design method for adaptive structures. After a brief derivation of the influence matrices, the methodology is illustrated using three basic bracing systems – a truss, a frame and a diagonally braced frame – as example, demonstrating the relationship between structural topology and inherent adaptability. While the assessment of an adaptive structure's quality depends on the specific use case and control objective, it is proposed that truss systems are good candidates for adaptive structures due to their inherent adaptability.